A chemical genetic approach to probe the function of PINK1 in regulating mitochondrial dynamics - Zhang, Conggang; Lee, Schuyler; Peng, Yinghua; Bunker, Eric; Shen, Chong; Giaime, Emilie; Shen, Jie; Shen, Jingshi; Zhou, Zongyao; Liu, Xuedong (Cell research, 2015)
Dear Editor, PINK1 and Parkin have been implicated in mitochon- drial quality control, mitochondrial fusion/fission dynamics and axonal mitochondrial mobility in neurons [1, 2]. The PINK1-Parkin pathway is very dynamic and the biological responses mediated by the PINK1-Parkin pathway differ spatially and kinetically in different cell types [2]. Therefore, tools to dynamically probe the function of the PINK1-Parkin pathway are highly desirable. Here we report a chemical genetic approach to probe the function of PINK1 in mitophagy and mitochondrial mobility. Our results validate the roles of PINKI in recruitment of Parkin to mitochondria, mitochondrial mobility in neurons, and mitochondrial fusion/fission dynamics. In addition, we reveal that PINK1 is required for triggering Parkin translocation to mitochondria, but is dispensable for sustaining Parkin accumulation and consequent mitophagy.